The Defensive Methods Against Deepfake: Review - Talib, Ebtehal; Hassan, Nidaa Flaih; Jamil, Abeer Salim (Iraqi Journal of Science, 2023)
Due to the spread of “Deepfake” in our society and the impact of this phenomenon on politicians, celebrities, and the privacy of individuals in particular, as well as, on the other hand, its impact on the electoral process as well as financial fraud, all these reasons prompted us to present a research paper dealing with this phenomenon. This paper presents a comprehensive review of Deepfake, how it is created, and who has produced it. This paper can be used as a reference and information source for the methods used to limit deepfake by detecting forgeries and minimizing its impact on society by preventing it. This paper reviews the results of much research in the field of deepfake, as well as the advantages of each method, as well as finding points of weakness such as complexity, time consumption, and the environment that is applied to it. Methods to avoid or reduce these obstacles are also suggested.